Effect EFFECT OF CROP SPACING AND INORGANIC FERTILIZER DOSAGE ON PURPLE EGGPLANT PRODUCTION - Dora Nurshanti; Etha Widya Pramesti Aldha; Yulhasmir (Agriculture, 2026)
ABSTRACT The purple eggplant (Solanum melongena L.) is a vegetable crop belonging to the Solanaceae family. Managing planting spacing and applying adequate, balanced inorganic NPK fertilizer are cultivation techniques that can support plant growth and production. This study was conducted at the Experimental Garden of the Faculty of Agriculture, University of Baturaja, Ogan Komering Ulu Regency, from November 2025 to January 2026. The materials used were 'Yupita F1' variety purple eggplant seeds and NPK fertilizer. A Factorial Randomized Block Design (RBD) with two factors was employed. The first factor consisted of three planting spacing levels: J1 = 50 x 70 cm, J2 = 60 x 70 cm, and J3 = 70 x 70 cm. The second factor consisted of three NPK fertilizer dosages: P1 = 100 kg/ha, P2 = 200 kg/ha, and P3 = 300 kg/ha. Observed variables included time to flowering, shoot fresh weight, shoot dry weight, fruit weight per plant, fruit length per plant, and number of fruits per plant. Data were analyzed using the F-test and the Least Significant Difference (LSD) test at the 5% level. A planting spacing of 60 x 70 cm was the best treatment for purple eggplant growth and production. An NPK fertilizer dosage of 200 kg/ha was the best dosage for purple eggplant growth and production. Keyword: water, nutrients, competition, sunlight, plants